A Multicenter Single-Arm Objective Performance Criteria Trial to Determine the Efficacy and Safety of High-Frequency Irreversible Electroporation as Primary Treatment for Localized Prostate Cancer: A Study Protocol - He, Bi-Ming; Xue, Wei; Yan, Wei-Gang; Yin, Lei; Dong, Bai-Jun; Zhou, Zhi-En; Lin, Heng-Zhi; Zhou, Yi; Wang, Yan-Qing; Shi, Zhen-Kai; Zhou, Hai; Wang, Shuai-Dong; et al. (Frontiers in Oncology, 2021)
Introduction The classical pathway for the therapy of low to intermediate-risk localized prostate cancer is radical prostatectomy or radiation therapy, which has been shown a high incidence of complications, including erectile dysfunction, urinary incontinence, and bowel injury. An alternative pathway is to perform an ablation by some energy to the localized lesion, known as focal therapy. Irreversible High-frequency irreversible electroporation (H-FIRE) is nonthermal energy can be used in cancer ablation, to deliver pulsed high-voltage but low-energy electric current to the cell brane and then invoking cell death. An H-FIRE pathway has reported being tissue selective which lead to fewer side effects. Methods and analysis This is a multi-centre and single-arm objective performance criteria (OPC) study in which all men with a localized prostate cancer are allocated to H-FIRE ablation. This trial will assess the efficacy and safety of the H-FIRE pathway in the therapy of prostate cancer. Efficacy will be assessed by prostate biopsy 6 months after treatment while safety will be assessed by adverse events report and questionnaires. The main inclusion criteria are a moderate to low risk prostate cancer in D’Amico NCCN risk classification and had no previous therapy for prostate cancer. A sample size of 110 participants is required. The primary objective is to determine whether the detection rate of clinically significant cancer by prostate biopsy is less than 20% after the H-FIRE ablation. Ethics and dissemination This study has been obtained ethical approval by the ethics committee of all participating centres. The results of the study will be submitted for dissemination and publication in peer-reviewed journals. Conclusions This multi-centre single-arm objective performance criteria trial will evaluate the efficacy and safety of the use of high-frequency irreversible electroporation in treating prostate cancer.